Coloration mechanism of CsI(Tl) under irradiation; 3rd International Congress on Radiation Physics and Chemistry of Condensed Matter, High Current Electronics and Modification of Materials with Particle Beams and Plasma Flows - Alekseev V. D. Vadim Dmitrievich; Trefilova L. N. Larisa Nikolaevna; Yakovlev V. Yu. Viktor Yurjevich; Мелешко А. А. Анна Алексеевна; Charkina T. A. Tamara Aleksandrovna (2012, 2012)
Title screen